Pengaruh Pelarut Metanol terhadap Alumunium sebagai Wadah Obat Salep Mata - Widodo, Hernowo; Warta, Joni; Ulfah, Maria; Annisa, Amaliah (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2019)
Corrosion is a decrease in the quality of a material or metal due to electrolyte reactions in the environment that affect the life of the material. Corrosion rate is the speed of propagation or speed of decline in the quality of a material with time. Corrosion processes occur in acidic environments, sea water, rain water, and soil are the result of chemical reactions that are also caused by electrochemical processes. The purpose of this study is to determine the corrosion resistance of aluminum metal to variations in the solution of Methanol (CH3OH). This study uses aluminum plates that will be immersed 5 days with a solution of Methanol (CH3OH). How to collect data by testing the Scanning Electron Microscopy (SEM) on each aluminum plate specimen that has been treated with corrosion by heating at a temperature of 60 oC. Methanol solution is one of the factors causing corrosion of metals. If in the free environment, air, temperature, and acidic substances are most commonly found as a factor causing corrosion. The increased corrosion rate is due to the higher concentration of the cause of corrosion. In this discussion Methanol as the concentration used, and aluminum as the metal tested.